2015
DOI: 10.1615/jlongtermeffmedimplants.2015011749
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Damage of Collagenous Tissues: Experiment, Modeling and Simulation Studies

Abstract: Mechanical fatigue damage is a critical issue for soft tissues and tissue-derived materials, particularly for musculoskeletal and cardiovascular applications; yet, our understanding of the fatigue damage process is incomplete. Soft tissue fatigue experiments are often difficult and time-consuming to perform, which has hindered progress in this area. However, the recent development of soft-tissue fatigue-damage constitutive models has enabled simulation-based fatigue analyses of tissues under various conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 103 publications
1
9
0
2
Order By: Relevance
“…These fatigue-induced changes are thought to play a role in the pathogenesis of body tissues, leading to neck pain. 28,29 Increased daily walking steps in sedentary workers may indirectly reflect frequent rest breaks, allowing sufficient tissue recovery to occur. In addition, previous studies have shown that exercise, for example, cycling, can increase blood flow or tissue oxygenation to non-working or inactive muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fatigue-induced changes are thought to play a role in the pathogenesis of body tissues, leading to neck pain. 28,29 Increased daily walking steps in sedentary workers may indirectly reflect frequent rest breaks, allowing sufficient tissue recovery to occur. In addition, previous studies have shown that exercise, for example, cycling, can increase blood flow or tissue oxygenation to non-working or inactive muscles.…”
Section: Discussionmentioning
confidence: 99%
“…If there is insufficient time for allowing tissue capacity regeneration, the muscle fatigue may further reduce available capacity. These fatigue‐induced changes are thought to play a role in the pathogenesis of body tissues, leading to neck pain . Increased daily walking steps in sedentary workers may indirectly reflect frequent rest breaks, allowing sufficient tissue recovery to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, вследствие значительной асимметричной деформации стоек каркаса с изменением угла наклона и растяжением биологической ткани под действием интенсивной циклической нагрузки в процессе функционирования в организме пациента в створках биопротеза происходит перераспределение напряжения. При этом циклическое напряжение неизбежно приводит к усталости биоматериала, которая локализована в куполе и комиссуральной зоне створок [12]. По данным настоящего исследования, основная масса кальцификатов была расположена именно в зонах, более подверженных усталости.…”
Section: Discussionunclassified
“…Considering the urinary tract's hydrodynamic features, matters of concern are potential determinants of long‐term biomaterial fatigue, that is, continuous flow and related volume extensibility during the storage phase. Before implementation, a fatigue test could easily reveal the durability of the fabricated neo‐tissue; however, no published studies characterized fatigue in the preclinical tissue engineered graft . Of utmost importance in reconstructive therapies dedicated to young patients with a long‐life expectancy is fatigue analysis.…”
Section: Challenges For Future Translation Into Clinic ‐ the Need Formentioning
confidence: 99%